Bourbon Desserts. - Hulsman, Lynn Marie (The University Press of Kentucky, 2014)
The flavor of bourbon adds flair and sophistication to every occasion. Celebrations in the Bluegrass State? or any state, for that matter? are never complete without the unique richness of this signature drink. Every holiday party is made warmer with bourbon balls and velvety bourbon eggnog, and no respectable Kentucky Derby party is complete without ice-cold mint juleps. Bourbon Desserts features more than seventy-five decadent desserts using America's native spirit. Celebrated food writer and home chef Lynn Marie Hulsman brings together a collection of confections highlighting the complex flavor notes of Kentucky bourbon, which are sure to delight the senses. Organized by category and beautifully presented, the delectable recipes include Bourbon Cr?me Brulee, Watermelon Julep Pops, Drunken Hot-Fudge Pudding Cake, Derby Morning Maple-Bourbon Hotcake Syrup, and Grandma Rose's Big Race Pie. Giving readers the confidence to prepare these easy-to-execute desserts, this cookbook also features fun facts about bourbon and its origins as well as tips and tricks for working in the kitchen. Designed for the amateur boozy baker but sophisticated enough for the culinary professional, the indispensable collection of recipes in Bourbon Desserts proves an old saying: "What whiskey and butter won't cure, there's no cure for."